Lipid profiling in maternal and fetal circulations in preeclampsia and fetal growth restriction-a prospective case control observational study - Thushari I. Alahakoon; Heather J. Medbury; Helen Williams; Vincent W. Lee (BMC, 2020)
Abstract Background While many risk factors for preeclampsia, such as increased body mass index, advanced maternal age, chronic hypertension, diabetes, are now established in clinical practice, maternal lipid profile has not been included in the risk assessment for preeclampsia. We aim to characterize the serum levels of Total Cholesterol (TC), High density lipoprotein (HDL), Low density lipoprotein (LDL), Triglycerides (TG), Apolipoprotein A1, Apolipoprotein B and their ratios TC/HDL and ApoB/ApoA1 in the maternal and fetal circulations of normal pregnancy, preeclampsia (PE), fetal growth restriction (FGR) and PE + FGR. Methods A prospective cross-sectional case control study was conducted measuring maternal and fetal lipid levels by enzymatic analysis and immune-turbidimetric enzymatic assays. FGR was defined by elevated umbilical artery Doppler resistance in association with estimated fetal weight < 10%. Kruskal Wallis non-parametric analysis of variance was used to test for homogeneity across the clinical groups for each of the variables, Mann-Whitney tests for pairwise comparisons and Spearman rank correlation were used to quantify gestational age-related changes. Results (1) TG levels were elevated in maternal PE and cord blood PE + FGR groups compared to normal pregnancies. (2) A statistically significant elevation of fetal ApoB levels was observed in PE, FGR and PE + FGR compared to normal pregnancies. Apolipoprotein levels A1 and B were not different between maternal groups. (3) TC, HDL, LDL and TC/HDL levels did not show any significant gestational variation or between clinical groups in the maternal or fetal circulation. Conclusions Elevation in maternal TG levels may have a role in the pathogenesis of PE. The implications of elevated maternal and fetal TG levels and elevated fetal Apolipoprotein B levels deserves further exploration of their role in long term cardiovascular risk in the mother as well as the offspring.